Real Life Monitoring of Conveyor Line Speed Using IoT and Raspberry Pi - Al-Shahethi, M.G. (Institute of Electrical and Electronics Engineers Inc., 2021)
Manual monitoring is time-consuming and frustrates the industry with high costs and delays in the process. This study presented a remote monitoring system for a direct current (DC) motor based on Internet of Things (IoT) for safe and economic data communication in industrial fields. A single sensor monitors the DC motor speed and sends it to the Raspberry Pi microcontroller, which sends it to the cloud database for remote monitoring. The system also presents the manual control methods to adjust the motor speed using a simple potentiometer. Therefore, the proposed system has three functions: measuring, monitoring, and controlling. Measuring is based on an optoisolator sensor and an Arduino Mega microcontroller. Controlling is based on the Potentiometer, Arduino Uno, and a motor drive circuit. Monitoring is based on Raspberry Pi and ThingSpeak platform. Firstly, the speed sensor HC-020K senses the speed Data. Secondly, Arduino Mega extracts the HC-020K sensor's data as a suitable revolution per minute and sends it to Raspberry Pi. Thirdly, Raspberry Pi sends the data to ThingSpeak's Server. Lastly, based on the experiments performed, the system has proved to be very useful and reliable. Â© 2021 IEEE.